PEMODELAN GENERALIZED POISSON REGRESSION PADA KASUS AIDS DI PROVINSI NUSA TENGGARA TIMUR TAHUN 2023 - GUNTUR, Robertus; Dappa, Jelita Susanti Bili (Program Studi Statistika Fakultas MIPA UNM, 2024)
East Nusa Tenggara (ENT) Province is one of the contributors to the high number of AIDS cases in Indonesia. The purpose of study is to analyse the factors affecting the number of AIDS cases in the Province using the Generalized Poisson Regression method. The variable used is the number AIDS cases as a response variable, and seven predictor variables that might be influence the response variable. The data obtained from the publications of the Central Statistics Agency of ENT Province in 2024. The study shows that the GPR model applying six predictors yields the best model with value of AIC is 419.93. Those variables are the number of health facilities , the number of poor people , the human development index , sexually transmitted infections , the number of adolescents aged 15-24 years who received reproductive health counselling , and the open unemployment rate